Gestión integral de residuos químicos generados en actividades industriales - Loayza-Pérez, Jorge; Silva-Meza, Marina (Pontificia Universidad Católica del Perú, 2009)
Integral management of chemical wastes generated in industrial activitiesThe integral management of chemical wastes allows to d iminish the amount of generated wastes, to reutilize wastes so as to diminish their danger, and to make safe use of the final disposition of those wastes that cannot be reduced. Here we present the principies of chemical wastes management, the analysis of the service I ife of a waste and diverse treatment options (physical, chemical, thermal and biological) for its final disposition

La gestión integral de residuos químicos permite minimizar la cantidad de residuos generados, reaprovechar los residuos que puedan volver a ser utilizados, tratarlos para disminuir su peligrosidad, y real izar una disposición final segura de aquellos residuos que no puedan ser reducidos. Se presentan los principios de gestión, el análisis del ciclo de vida de un residuo y diversas opciones de tratamiento (físico, químico, térmico y biológico) para la disposición final.
Keywords: Chemistry; Hazardous Waste; Physical Treatment; Chemical Treatment; Thermal Treatment; Biological Treatment; Química; Residuo Peligroso; Tratamiento Físico; Tratamiento Químico; Tratamiento Térmico; Tratamiento Biológico; https://purl.org/pe-repo/ocde/ford#1.04.00